2021
DOI: 10.1021/acsami.1c14133
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nanodiamond Grains in the Exfoliation of WS2 Nanosheets and Their Enhanced Hydrogen-Sensing Properties

Abstract: Herein, for the first time, a combination of detonation nanodiamond (DND)–tungsten disulfide (WS2) was devised and studied for its selective H2-sensing properties at room temperature. DND–WS2 samples were prepared by a sonication-assisted (van der Waals interaction) liquid-phase exfoliation process in low-boiling solvents with DND as a surfactant. The samples were further hydrothermally treated in an autoclave under high pressure and temperature. The as-prepared samples were separated as two parts named DND–WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The WS 2 -based heterojunction can be an effective strategy in improving the sensing performance at room temperature. In case of chemoresistive gas sensors, WS 2 -based nanostructures such as 2D nanoflakes, [130,131] and nanosheets [132][133][134][135][136][137] are widely utilized due to the facile control of nanostructure morphology and numerous edge sites. The exposure of edge sites of 2D nanostructures is proven beneficial in chemoresistive gas sensing, which was reported in several research works.…”
Section: Tmds and Othersmentioning
confidence: 99%
“…The WS 2 -based heterojunction can be an effective strategy in improving the sensing performance at room temperature. In case of chemoresistive gas sensors, WS 2 -based nanostructures such as 2D nanoflakes, [130,131] and nanosheets [132][133][134][135][136][137] are widely utilized due to the facile control of nanostructure morphology and numerous edge sites. The exposure of edge sites of 2D nanostructures is proven beneficial in chemoresistive gas sensing, which was reported in several research works.…”
Section: Tmds and Othersmentioning
confidence: 99%
“…For these reasons, TMDCs have been investigated as active materials for several years [ 15 ], with MoS 2 and WS 2 as the two most studied TMDCs. While MoS 2 has been reported mainly as useful for detecting NO 2 and NH 3 [ 19 ], WS 2 has been found useful for detecting NH 3 [ 20 ], NO 2 [ 21 , 22 , 23 ], H 2 S [ 21 , 24 , 25 ], or H 2 [ 26 , 27 ]. Therefore, WS 2 is a good candidate material for detecting hydrogen at moderate operating temperatures or even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Sensing mechanisms can involve many changes, such as charge transfer and doping, intercalation, and shifts in permittivity and lattice vibrations [ 17 ]. However, recent theoretical studies show that the gas sensing mechanisms of TMDCs and related layered materials have charge transfer processes as the main route for detecting gases [ 27 , 28 , 29 , 30 ], in which the sensing materials act as charge acceptors or donors [ 4 , 28 , 29 , 30 ]. For example, Changjie Zhou et al reported that hydrogen adsorption brings a relatively small amount of charge transfer from the WS 2 monolayer to the adsorbed hydrogen molecule [ 31 ].…”
Section: Introductionmentioning
confidence: 99%